Contested identities : Catholic women religious in nineteenth-century England and Wales - Mangion, Carmen M. (Book collections on Project MUSE., 2019)
English Roman Catholic women's congregations are an enigma of nineteenth-century social history. Over ten thousand nuns and sisters, establishing and managing significant Catholic educational, health care and social welfare institutions in England and Wales, have virtually disappeared from history. Despite their exclusion from historical texts, these women featured prominently in the public and private sphere. Intertwining the complexities of class with the notion of ethnicity, Contested identities examines the relationship between English and Irish-born sisters. This study is relevant not only to understanding women religious and Catholicism in nineteenth-century England and Wales, but also to our understanding of the role of women in the public and private sphere, dealing with issues still resonant today. Contributing to the larger story of the agency of nineteenth-century women and the broader transformation of English society, this book will appeal to scholars and students of social, cultural, gender and religious history.